Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.cbpa.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the optical control of protein function through genetic code expansion

Abstract: In nature, biological processes are regulated with precise spatial and temporal resolution at the molecular, cellular, and organismal levels. In order to perturb and manipulate these processes, optically controlled chemical tools have been developed and applied in living systems. The use of light as an external trigger provides spatial and temporal control with minimal adverse effects. Incorporation of light-responsive amino acids into proteins in cells and organisms with an expanded genetic code has enabled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
99
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 57 publications
0
99
0
Order By: Relevance
“…However, none of the mutants we screened retained sufficient activity to yield DAG production upon recruitment, whilst also showing low basal activity before recruitment. We also attempted to incorporate caged lysine into the L. monocytogenes enzyme using unnatural amino acids (Courtney and Deiters, 2018), though were unable to obtain expression of the mutated enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…However, none of the mutants we screened retained sufficient activity to yield DAG production upon recruitment, whilst also showing low basal activity before recruitment. We also attempted to incorporate caged lysine into the L. monocytogenes enzyme using unnatural amino acids (Courtney and Deiters, 2018), though were unable to obtain expression of the mutated enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…gene activation and silencing, 1 or protein interactions. 2 Because of many potential non-invasive applications with enhanced selectivity, light controlled activation of biologically active compounds, such as antibiotics, 3,4 anticancer agents, 5 neurotransmitters, 6 amino acids or proteins 7 and kinase inhibitors 8 is currently being explored. 9 Since their introduction by Engels and Schlaeger 10 for the protection of adenosine, PPGs have been extensively studied, and several key aspects have been determined as being crucial for their applicability in biological systems.…”
mentioning
confidence: 99%
“…We found that expression of LepB led to substantial PI3P depletion from cells, and consequent swelling of the endosomal compartment that depends on this lipid for function (B.D.G and G.R.V.H., unpublished observations). Therefore, to induce acute LepB activity, we turned to an optogenetic approach that utilizes genetic code expansion to incorporate an unnatural, caged amino acid into the protein (Luo et al, 2014;Liu et al, 2017;Courtney and Deiters, 2018).…”
Section: Pi(34)p2 Is Sufficient For Cphx3 Cellular Localizationmentioning
confidence: 99%